2020
DOI: 10.1101/2020.08.24.264580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anin vitrotumorigenesis model based on live cell-generated oxygen and nutrient gradients

Abstract: The tumor microenvironment (TME) is multi-cellular, spatially heterogenous, and contains cell-generated gradients of soluble molecules. Current cell-based model systems lack this complexity or are difficult to interrogate microscopically. We present a 2D live-cell chamber that approximates the TME and demonstrate that breast cancer cells and macrophages generate hypoxic and nutrient gradients, self-organize, and have spatially varying phenotypes along the gradients, leading to new insights into tumorigenesis.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Our earlier work has shown that murine 4T1 tumor cells can express high Nos2 and Cox2 levels and that Nos2/Cox2 blockade limited tumor growth (16, 17). Thus, 4T1 tumor bearing mice are representative of NOS2 Hi /COX2 Hi breast tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Our earlier work has shown that murine 4T1 tumor cells can express high Nos2 and Cox2 levels and that Nos2/Cox2 blockade limited tumor growth (16, 17). Thus, 4T1 tumor bearing mice are representative of NOS2 Hi /COX2 Hi breast tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Microfluidic systems have been used to expose cells to different levels of ambient O 2 while simultaneously imaging the fluorescence intensity of ROS sensitive fluorescent probes 20 . Alternatively, cell culture chambers that restrict gas exchange with the environment have been used to create cell-generated oxygen gradients, and to image hypoxic gradients and other relevant parameters, such as mitochondrial membrane potential 21,22 .…”
Section: Openmentioning
confidence: 99%